The Limited Clinical Utility of Testosterone, Estradiol, and Sex Hormone Binding Globulin Measurements in the Prediction of Fracture Risk and Bone Loss in Older Men. (14th November 2016) - Orwoll, Eric S; Lapidus, Jodi; Wang, Patty Y; Vandenput, Liesbeth; Hoffman, Andrew; Fink, Howard A; Laughlin, Gail A; Nethander, Maria; Ljunggren, Östen; Kindmark, Andreas; Lorentzon, Mattias; Karlsson, Magnus K; et al.
ABSTRACT: Measurement of serum testosterone (T) levels is recommended in the evaluation of osteoporosis in older men and estradiol (E2) and sex hormone binding globulin (SHBG) levels are associated with the rate of bone loss and fractures, but the clinical utility of sex steroid and SHBG measurements for the evaluation of osteoporosis in men has not been examined. To evaluate whether measurements of T, E2, and/or SHBG are useful for the prediction of fracture risk or the rate of bone loss in older men, we analyzed longitudinal data from 5487 community‐based men participating in the Osteoporotic Fractures in Men (MrOS) study in the United States, Sweden, and Hong Kong. Serum T, E2, and SHBG levels were assessed at baseline; incident fractures were self‐reported at 4‐month intervals with radiographic verification (US), or ascertained via national health records (Sweden, Hong Kong). Rate of bone loss was assessed by serial measures of hip bone mineral density (BMD). We used receiver operating characteristic (ROC) curves, net reclassification improvement (NRI), and integrated discrimination improvement (IDI) to assess improvement in prediction. Mean age at baseline was 72 to 75 years and the prevalence of low T levels (<300 ng/dL) was 7.6% to 21.3% in the three cohorts. There were 619 incident major osteoporotic and 266 hip fractures during follow‐up of approximately 10 years. Based on ROC curves, there were no improvements in fracture risk discrimination for any biochemical measure when added to models, including the Fracture Risk Assessment Tool (FRAX) with BMD. Although minor improvements in NRI were observed for the dichotomous parameters low bioavailable E2 (BioE2) (<11.4 pg/mL) and high SHBG (>59.1 nM), neither sex steroids nor SHBG provided clinically useful improvement in fracture risk discrimination. Similarly, they did not contribute to the prediction of BMD change. In conclusion, there is limited clinical utility of serum E2, T, and SHBG measures for the evaluation of osteoporosis risk in elderly men. © 2016 American Society for Bone and Mineral Research.